The effects of Gymnema sylvestre extract supplementation on expression of gene associated with glucose homeostasis in diabetic mouse model. - Nguyen, Duc Quan; Tran, Thi Kim Anh; Do, Thi Trang; Tran, Thi Huong Giang; Do, Thi Thanh Trung; Le, Tat Thanh; Nguyen, Huy Hoang (Vietnam Journal of Biotechnology, 2025)
Gymnema sylvestre, a traditional medicinal herb known for its anti-diabetic properties, has been widely used to manage hyperglycemia by various mechanisms, including the inhibition of glucose absorption, stimulation of insulin secretion, and enhancement of pancreatic beta-cell regeneration. In the context of the increasing prevalence of diabetes, particularly in Vietnam, this study investigates the molecular effects of G. sylvestre extract (gymnemic acid) on gene expression associated with glucose homeostasis in diabetic mouse models induced by streptozotocin. The expression levels of key regulators involved in glucose transport, insulin production, and inflammatory responses, such as GLUT2, MAFA, INS2, PDX1, NFKB, and GCK, were evaluated using RT-qPCR analysis. Our findings indicated that diabetic mice, receiving 250 mg of G. sylvestre extract per kg of body weight daily for 6 weeks, exhibited significant improvements in glucose regulation when compared to their counterparts on a high-fat diet. This result was evidenced by increased gene expression related to insulin secretion and glucose uptake, alongside a decrease in body weight and blood glucose levels in diabetic mice. These beneficial outcomes can be attributed to the role of gymnemic acid in supporting various processes, including competitive inhibition of glucose absorption, enhancement of insulin secretion, protection and regeneration of pancreatic beta-cells, and improvement of lipid metabolism. Collectively, these findings highlight the potential of G. sylvestre as a nutrigenomic intervention in diabetes management through its regulation of key metabolic pathways.